(untitled) (Fiep Bulletin - online, 2019)
Occupational stress is considered one of the most frequent mental and behavioral disorders in the population. Theregular practice of physical exercise is a non-drug option for the treatment and prevention of stress and other mental disorders.the aims to compare the manifestation of stress among military police officers who practice and don’t practice physical exercisesin the Patos-PB city. It’s a field research, Survey, with a quantitative approach, a descriptive purpose, a non-probabilistic andintentional sample. Sample whit 60 policemen of the Patos - PB city, into sedentary and active people. The instrument used be asemi structured socioeconomic questionnaire and the Inventory of Stress Symptoms for Adults of Lipp (ISSL). The data wasanalyzed through Microsoft Excel. Of the 30 sedentary subjects, 15 are in the Resistance Phase, 15 sedentary individuals in theExhaustion Phase. Of the 30 active subjects, 21 are absent from stress, only 1 active individual is in the Alert Phase, another 7active subjects are in the Resistance Phase and only 1 individual in Phase III. The groups of militaries non – practicing physicalexercise have symptoms of stress, while the groups of military policemen practicing physical are largely free of stress. Therefore,physical exercise exerts a strong influence on the control of stress.